Bridging the gap: The perceptions of athletic directors and coaches regarding nonrevenue program discontinuation decisions - Erianne A. Weight; Coyte G. Cooper (Journal of Applied Sports Management, 2011)
The purpose of this study was to explore the perceptions of athletic directors and coaches regarding wrestling program discontinuation decisions. In the past few decades, an alarming number of NCAA men’s wrestling programs have been eliminated throughout the United States (Student-athlete, 2006). Historically, the educational value offered through intercollegiate athletics was enough to justify financial funding of these programs; however, the marked trend toward the discontinuation of sports that are nonrevenue in nature support the notion that this justification may no longer be sufficient in today’s big-time intercollegiate athletic environment. In order to ensure the sustainability of programs that do not have the financial lure of big-time football and basketball, it is essential for primary program advocates (coaches) to understand the criteria employed by athletic directors when eliminating these programs. Utilizing a multiple-embedded case study (n = 4) with the use of survey, athletic directors (n = 20) and wrestling head coaches (n = 24) of Football Bowl Subdivision universities who have sponsored wrestling within the past ten years were studied in order to explore perceptions regarding the criteria utilized in programtermination decisions. Findings suggest that athletic directors utilize budget shortages and financial strain of the program as primary discontinuation criteria followed by gender equity implications, success on the mat, and regional sport popularity. In contrast, the coaches indicated they felt gender equity, regional sport popularity, donor support, athletes’ actions off the mat, and athletes’ academic performance were the primary reasons for program eliminations. Thus, the results illustrated that athletic directors and coaches had varying perceptions for the reasons why nonrevenue programs such as men’s wrestling are eliminated. The study provides a unique opportunity to understand the underlying reasons why men’s wrestling programs are eliminated, and what coaches of nonrevenue sports might do to sustain their programs.
Keywords: NCAA; program eliminations; men’s wrestling; athletic director decisions